Leuconidae (Crustacea: Cumacea) from the collections of the Museum Victoria, Australia - Gerken, Sarah (Zootaxa, 2016)
The collections of the Museum Victoria have yielded six new leuconid species in five genera from Australian waters: Austroleucon adiazetos n. sp., A. dolosolevis n. sp., Eudorellopsis mykteros n. sp., Kontiloleucon australiensis n. gen., n. sp., Leucon (Alytoleucon) dolichorhinos n. sp., Ommatoleucon megalopos n. sp. as well as the new genus Kontiloleucon. Leucon (Leucon) echinolophotos n. sp. is a new species from off Enderby Land, Antarctica. Keys to the Australian leuconid genera and species are included.